2013
DOI: 10.1108/nlw-05-2013-0044
|View full text |Cite
|
Sign up to set email alerts
|

Putting QR codes to the test

Abstract: 2014),"The plan behind the scan: using QR codes as a service and marketing tool", LibraryIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…In a classroom experiment with 20 students and three instructors, Li, Tan and Chou 10 found that the majority of the subjects found using QR codes in a classroom management system very easy. In a focus study with 28 library patrons, Lo and Coleman 24 found perceived ease of use regarding QR codes to be high, and they suggested that it could be enhanced by providing instructions for those who are unfamiliar with the technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a classroom experiment with 20 students and three instructors, Li, Tan and Chou 10 found that the majority of the subjects found using QR codes in a classroom management system very easy. In a focus study with 28 library patrons, Lo and Coleman 24 found perceived ease of use regarding QR codes to be high, and they suggested that it could be enhanced by providing instructions for those who are unfamiliar with the technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The survey provided a picture of the awareness and use of QR codes in libraries. A survey conducted by Lo et al (2013) indicated that the patrons found QR codes easy to use in libraries. Xu (2014) in their study mentioned that the use of QR codes in libraries will increase in the future.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lo Leo, Coleman and Danielle (2013) gave the experts a framework to overview the utilization of QR codes also as what the libraries could give on that stage. The makers found that allies generally find QR codes easy to use and would welcome a collection of library organizations on their PDAs.…”
Section: Literature Reviewmentioning
confidence: 99%